KINSHIP OF SIBOLGA COASTAL MALAY AND MANDAILING LANGUAGE: STUDY OF LEXICOSTATISTICS - Nasution, Tanty Aidullia; Widayati, Dwi; Lubis, Tasnim (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2025)
This study explores the linguistic kinship between the Sibolga Coastal Malay and Mandailing languages using the lexicostatistical method. Both languages belong to the Austronesian family and are spoken in close geographical proximity, raising questions about their historical relationship. By utilizing a 200-word Swadesh list, the research identifies shared lexical items and phonemic correspondences between the two languages. The findings reveal a lexical similarity of 38%, classifying the two as part of the same language family. Based on the lexicostatistical formula, the separation between the two languages is estimated to have occurred around 2,230 years ago, or approximately between 382 and 32 BCE, considering a standard error margin. This suggests that Sibolga Coastal Malay and Mandailing evolved from a common proto-language, with divergence influenced by geographical and sociocultural factors. The study provides valuable insight into historical language development in North Sumatra and emphasizes the importance of comparative linguistics in tracing the evolution of regional languages. These results also support the hypothesis that Malay and Mandailing linguistic features have undergone gradual yet distinct phonological and lexical changes over time.